FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN KONSUMEN PRIMER - Silvia, Silvia; Surjadi, Lukman (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This study aims to know about effect of profitability, liquidity, leverage, firm size, and managerial ownership on firm value in primary consumer goods companies listed on IDX during the period of 2019-2021. This study used a purposive sampling method with a total sample of 21 companies. The sample data was processed using the Eviews 12 Student Version software. The results showed that profitability and leverage have a positive effect on firm value, liquidity has no positive effect on firm value, and firm size and managerial ownership have no negative effect on firm value.